2005
DOI: 10.1152/ajpendo.00195.2005
|View full text |Cite
|
Sign up to set email alerts
|

Acute inhibition of lipolysis does not affect postprandial suppression of endogenous glucose production

Abstract: To test the hypothesis that intrahepatic availability of fatty acid could modify the rate of suppression of endogenous glucose production (EGP), acipimox or placebo was administered before and during a test meal. We used a modified isotopic methodology to measure EGP in 11 healthy subjects, and 1 H magnetic resonance spectroscopic measurement of hepatic triglyceride stores was also undertaken. Acipimox suppressed plasma free fatty acids markedly before the meal (0.05 Ϯ 0.01 mmol/l at Ϫ10 min, P ϭ 0) and throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…This observation is in accord with recent findings in humans (8). Importantly, our data show a significant reduction in liver enzymes and triglyceride levels, together with an improved hepatic insulin sensitivity, as computed from fasting measurements.…”
Section: Ajp-endocrinol Metabsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation is in accord with recent findings in humans (8). Importantly, our data show a significant reduction in liver enzymes and triglyceride levels, together with an improved hepatic insulin sensitivity, as computed from fasting measurements.…”
Section: Ajp-endocrinol Metabsupporting
confidence: 93%
“…By using the antilipolytic drug acipimox, Carey et al (8) showed recently that the improvement in glucose homeostasis induced by the drug was related to the content of fat in the liver, as measured before the administration of the agent. The assessment of liver fat content was not repeated after the intervention to test whether changes in this variable might be mediators of the systemic effects of the drug (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement, Tiikkainen et al (34) demonstrated that the hepatic fat content is more closely related to indexes of insulin resistance than degree of obesity. It is well documented that fatty liver fails to suppress glucose production in response to insulin in people both with and without diabetes (35)(36)(37). The question of whether hepatic insulin resistance is a consequence of increased liver fat or vice versa is a matter of a hectic debate (38).…”
Section: Discussionmentioning
confidence: 99%
“…Further, numerous studies have demonstrated that obesity, type 2 diabetes, dyslipidemia, hypertension, and insulin resistance are strongly associated with NAFLD [12,[19][20][21][22] . NAFLD also is strongly associated with hepatic, adipose tissue, and whole body reductions in insulin sensitivity, increased rate of gluconeogenesis, impaired insulin response to suppress gluconeogenesis, and impaired fatty acid oxidation [23][24][25] . However, the question about whether hepatic insulin resistance is a cause or a consequence of hepatic steatosis is unresolved [26][27][28] .…”
Section: And Nafldmentioning
confidence: 99%